Membrane, preparation method thereof and application of membrane in membrane decarburization of natural gas
By using hydrophilic materials instead of traditional silicone rubber during the decarbonization process of offshore natural gas membrane method, the problem of heavy hydrocarbon pollution on the surface of the membrane caused by CO2 throttling expansion is solved, and the separation performance and application stability of the membrane are significantly improved.
Patent Information
- Application Number
- CN202311572206.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-21
- Filing Date
- 2023-11-22
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2043-11-22
AI Technical Summary
During the decarbonization process of offshore natural gas membrane method, the cooling phenomenon caused by throttling expansion of CO2 and the large infiltration of CO2 oversaturation of heavy hydrocarbons in the membrane shell, thereby condensing on the membrane surface to form pollution, destroying the silicone rubber blocking holes, resulting in a sharp decline in membrane separation performance.
Hydrophilic materials are used to replace traditional silicone rubber, and defective holes on the surface of the membrane core are modified through hydrophilic modifiers to form a hole-blocking effect of the hydrophilic material, forming a stable hole-blocking effect, and improving the membrane's heavy hydrocarbon pollution resistance.
It significantly improves the long-term application stability of CO2 separation membrane, avoids membrane surface defects and degradation of separation performance caused by heavy hydrocarbon pollution, and reduces operating costs and energy consumption.
Smart Images

Figure SMS_1 
Figure HDA0004566234640000011 
Figure HDA0004566234640000012
Abstract
Description
Technical Field
[0001] The present application relates to a membrane and a preparation method thereof and application in natural gas membrane decarbonization, belonging to the field of membrane separation. Background Art
[0002] Natural gas is usually accompanied by an indefinite amount of CO2 during the extraction process, which not only reduces the calorific value of natural gas, increases transportation load and cost, but also corrodes pipelines and equipment. Therefore, decarbonization treatment must be carried out in the early stage to meet the national commercial gas standards. my country is rich in marine natural gas resources. The resources in Bohai Sea, East China Sea and the northern part of the South China Sea alone account for 15.6% of the total domestic resources. At present, the mature technology for natural gas decarbonization is the absorption tower process, which is widely used on land; but when used in the offshore natural gas decarbonization process, it shows obvious shortcomings, such as large size, high tower height, small operating elasticity range, serious impact on processing efficiency when shaking, and there are drawbacks such as mist entrainment, liquid flooding, and liquid leakage. In comparison, the membrane separation method has the advantages of low energy consumption, small footprint, simple process, and modular operation, and is expected to occupy a dominant position in the field of offshore platform natural gas decarbonization.
[0003] The natural gas produced by offshore platforms is often in a high-pressure state, and the CO2 content in some gas fields is relatively high. Taking a gas field in the South China Sea as an example, the pressure of the original natural gas produced reaches 6.0-7.0 MPa, of which the CO2 content is as high as 42.67%, methane is 46.12%, and the rest are nitrogen, ethane, propane, butane and heavy hydrocarbons. Therefore, when using membrane natural gas decarbonization, the CO2 partial pressure on the raw material side is as high as 2.0 MPa or more, and because CO2 is a condensable gas and has a high solubility coefficient in the polyimide membrane material, it is a gas that quickly permeates through the membrane. In this case, the large-scale permeation of CO2 from the high-pressure side to the low-pressure side will form a typical Joule-Thomson process, which will inevitably lead to a significant throttling expansion and cooling effect.
[0004] Taking the natural gas produced by a gas field in Hainan as an example, if operated at 323K, the CO2 partial pressure difference on both sides of the membrane will exceed 2.0MPa. In this case, the throttling expansion caused by CO2 throttling penetration will bring about a temperature drop of nearly 20.0℃. On the one hand, the heavy hydrocarbons contained in the natural gas permeate through the membrane and belong to "slow gas". Its concentration in the membrane module is much higher than the inlet value due to the large amount of CO2 permeation loss; at the same time, the accompanying cooling effect will further reduce the saturated vapor pressure of the heavy hydrocarbon components, making the heavy hydrocarbon content on the high-pressure side of the membrane module more and more supersaturated, and causing different degrees of pollution phenomena such as adsorption / condensation on the membrane surface.
[0005] In order to obtain high permeability flux with practical application value during the preparation of separation membranes, separation membranes are all asymmetric structures, and their surface dense separation layer is generally less than 0.1 microns. Such a thickness cannot be used to directly prepare defect-free separation membranes by phase inversion method. There are often a certain proportion of micro-defects on the surface, and silicone rubber coating plugging technology is required for post-treatment. After this treatment, the separation performance of the membrane will be close to or reach the intrinsic separation coefficient of the material. However, in the case of heavy hydrocarbon adsorption and swelling, the silicone rubber plugging part of the membrane surface will be destroyed, causing the surface defects of the separation membrane to reappear, resulting in a decrease in the membrane separation performance or even loss of separation performance.
[0006] In order to avoid the occurrence of heavy hydrocarbon contamination of membrane components, engineering designers often empirically increase the operating temperature of membrane components to 60.0-70.0℃. In some gas fields with high initial heavy hydrocarbon content, the operating temperature of membrane components is even as high as 90.0℃ or above. Although such a design can avoid the occurrence of heavy hydrocarbon contamination of membrane components to the greatest extent, its disadvantages are also obvious: first, high-temperature operation will bring additional heating energy consumption burden to offshore platforms; at the same time, long-term high temperature will seriously threaten the stable operation of membrane components, because the high-temperature resistance of the epoxy sealing head of the membrane component cannot be guaranteed for a long time; the most serious impact is the impact on the separation performance of the membrane component, because for glassy polymer membranes, the permeation flux of gas in them increases and the separation coefficient decreases at high temperatures, which will cause an unnecessary sharp increase in the methane loss rate, affecting the economic competitiveness of the membrane decarbonization process. Summary of the invention
[0007] In order to solve the problem that the silicone rubber plugging holes on the membrane surface are destroyed under heavy hydrocarbon pollution conditions, resulting in a decrease in membrane separation performance, this patent proposes a coating method for plugging defective holes on the surface of the separation membrane using hydrophilic materials, which can greatly alleviate the problem of membrane performance degradation and has obvious technical advantages.
[0008] In order to solve the problem that during the membrane decarbonization process of natural gas on offshore platforms, the cooling phenomenon caused by CO2 throttling expansion and the large-scale penetration of CO2 lead to the supersaturation of heavy hydrocarbons in the membrane shell, which then condenses on the membrane surface to form pollution and destroy the silicone rubber pores, causing a sharp decline in membrane separation performance, the present invention proposes a membrane coating method using hydrophilic materials instead of traditional silicone rubber.
[0009] According to one aspect of the present application, there is provided a membrane, which comprises a base membrane, a hydrophilic layer, and a hydrophilic functional coating in sequence;
[0010] The material of the hydrophilic layer is selected from at least one of ethanolamine, diethanolamine, diaminopropanol, diaminobenzoic acid, and 2,4-diaminobenzenesulfonic acid;
[0011] The material of the hydrophilic functional coating is selected from at least one of cellulose acetate, polyethylene glycol, chitosan, polyvinyl alcohol and polylactic acid.
[0012] The base film is selected from at least one of a polyimide film, a cellulose acetate film, and a polysulfone film.
[0013] According to another aspect of the present application, a method for preparing the above-mentioned membrane is provided, firstly, a hydrophilic modifier is used to perform hydrophilic modification on the defective pores on the surface of the hollow fiber membrane contained in the membrane core, so as to form affinity anchor points in the defective pores, so as to facilitate the subsequent hydrophilic material coating pore plugging process; after the membrane pores are hydrophilically modified, the membrane core diameter is cleaned and removed by the surface residual modification liquid, and then dried at high temperature to promote the hydrophilic modification process and fully remove the excess residual liquid in the membrane pores; then the membrane core is immersed in a coating liquid configured with a hydrophilic material, and a vacuum is drawn through the epoxy end of the membrane core to drive the coating liquid to penetrate into the membrane pores and combine with the affinity anchor points in the membrane pores to form a pore plugging effect of the hydrophilic material; after the coating is completed, the residual coating liquid on the surface is cleaned and removed, and then dried at high temperature and the cross-linking of the coating hydrophilic material is further promoted to form a stable pore plugging effect, so as to obtain a CO2 separation membrane that can withstand the damage caused by heavy hydrocarbon pollution commonly seen in the natural gas membrane decarbonization process.
[0014] The following steps are involved:
[0015] The base film is immersed I in a solvent I solution containing a hydrophilic modifier, dried I, and then immersed II in a solvent II solution containing a hydrophilic functional material and a cross-linking agent, and dried II to obtain the film.
[0016] The hydrophilic modifier is selected from at least one of ethanolamine, diethanolamine, diaminopropanol, diaminobenzoic acid, and 2,4-diaminobenzenesulfonic acid;
[0017] The solvent I is selected from at least one of methanol, ethanol and propanol; preferably ethanol.
[0018] In the solvent I solution containing the hydrophilic modifier, the concentration of the hydrophilic modifier is 0.01 to 10 wt %.
[0019] The vacuum degree of the impregnation I is 0-0.1 MPa;
[0020] The dipping time is 1 to 30 minutes;
[0021] The drying temperature is 50-120°C;
[0022] The drying time I is 1 to 120 minutes.
[0023] The hydrophilic functional material is selected from at least one of cellulose acetate, polyethylene glycol, chitosan, polyvinyl alcohol, and polylactic acid;
[0024] The cross-linking agent is selected from at least one of glutaraldehyde and boric acid;
[0025] The solvent II is selected from at least one of acetone, water and ethanol; preferably water.
[0026] In the solvent II solution containing the hydrophilic functional material and the cross-linking agent, the concentration of the hydrophilic functional material is 0.01 to 10 wt %;
[0027] In the solvent II solution containing the hydrophilic functional material and the cross-linking agent, the mass of the cross-linking agent is 5-25 wt % of the mass of the hydrophilic functional material.
[0028] The volume of the solvent II solution containing the hydrophilic functional material and the cross-linking agent is 2 to 5 times the volume of the base film;
[0029] The vacuum degree of the impregnation II is 0-0.1 MPa;
[0030] The immersion time of II is 1 to 30 minutes;
[0031] The temperature of the impregnation II is 0 to 100° C.;
[0032] The temperature of the drying II is 1 to 100° C.;
[0033] The drying time II is 1 to 120 minutes.
[0034] The drying I and drying II are carried out in a high-temperature vacuum oven.
[0035] The drying I and the drying II are preceded by washing.
[0036] The cleaning liquid used for cleaning is selected from at least one of water, ethanol and methanol;
[0037] The cleaning time is 1 to 30 minutes.
[0038] The specific steps are as follows:
[0039] According to the separation requirements, a certain number of bottom membranes are cast into a component core mode with a conventional end cap at one end and epoxy seal at the other end; depending on the separation processing volume, the number of membrane filaments can range from a few to hundreds of thousands;
[0040] Immerse the membrane core in the prepared hydrophilic modification liquid, introduce the modification liquid into the defective pores on the membrane surface by vacuuming the epoxy end, and then clean and remove the residual modification liquid on the surface. After a period of modification reaction, ensure that there are more affinity anchor points in the membrane micropores, and then place the membrane core in a drying oven for high-temperature treatment to fully remove the residual liquid in the membrane micropores;
[0041] After the membrane core is dried, it is immersed in the prepared hydrophilic coating liquid. The temperature of the hydrophilic coating liquid is kept high to facilitate the evaporation of the solvent. Then, vacuum is drawn at the epoxy end. On the one hand, the coating liquid is allowed to penetrate into the defective pores on the membrane surface. At the same time, the high-temperature solvent is allowed to continue to evaporate to increase the concentration of the hydrophilic material in the micropores to achieve the effect of plugging the pores. After a period of time, the change in vacuum is observed. If the vacuum degree is significantly reduced, it means that the defective pores on the membrane surface have been fully blocked. Then, the membrane core is immersed in the cleaning liquid while maintaining the vacuum degree to remove the residual coating liquid on its surface.
[0042] After cleaning, the membrane core is placed in a high-temperature drying oven and heated at a certain temperature for a fixed time so that the hydrophilic material in the membrane pores is fully cross-linked to form a stable pore blocking effect; at the same time, the residual liquid in the membrane micropores and on the surface is fully removed to prepare a membrane core resistant to heavy hydrocarbon pollution.
[0043] According to another aspect of the present application, an application of the above-mentioned membrane is provided for decarbonization of natural gas by membrane method.
[0044] The beneficial effects of this application include:
[0045] The present invention provides a method for coating the bottom membrane of a CO2 separation membrane with a hydrophilic material. Different from the conventional silicone rubber coating process, the hydrophilic material has a higher tolerance to heavy hydrocarbons, so that the CO2 separation membrane prepared by the present invention has better long-term application stability when applied to the natural gas decarbonization process. When heavy hydrocarbons condense on the membrane surface, the silicone rubber in the micropores of the CO2 separation membrane with silicone rubber coating plugging pores will swell and destroy its surface integrity. It is well known that the gas separation membrane must ensure a foolproof effect to achieve the separation function. Once the defective pores on the membrane surface are opened, the gas separation performance of the membrane will be sharply reduced or even completely lost, causing serious economic losses. In comparison, the hydrophilic material plugging method proposed by the present invention has very slight swelling of the hydrophilic material under heavy hydrocarbon pollution conditions, which can fully ensure the integrity and separation performance of the membrane surface. The process is simple, the raw materials are cheap, the reliability is good, and it has obvious technical advantages. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 (a), (b), (c), and (d) are electron microscope photos of uncoated polyvinyl alcohol films. Figure 1 (e), (f), (g), and (h) are electron microscope photos of the polyvinyl alcohol film after coating. The scale of (a) and (e) is 100 μm, the scale of (b) and (f) is 10 μm, and the scale of (c), (d), (g), and (h) is 1 μm.
[0047] Figure 2a This is a photo of a silicone rubber membrane immersed in petroleum ether for 20 minutes.
[0048] Figure 2b These are photos of polyvinyl alcohol films immersed in petroleum ether for 30 days. DETAILED DESCRIPTION
[0049] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0050] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0051] Example 1
[0052] A polyimide film was used as the base film. The base film was immersed in an ethanol solution containing 1wt% ethanolamine for 10 minutes, then the film was placed in a blast oven and dried at 70 degrees Celsius for 2 hours. The dried modified film was then immersed in a 2% polyvinyl alcohol aqueous solution. A certain vacuum degree was applied in the hollow tube of the film to drive the polyvinyl alcohol solution to penetrate into the micro-defect pores on the surface of the film. The coating time was 15 minutes. Then the coated film was placed in a blast oven and dried at 100 degrees Celsius for 2 hours to obtain a polyimide film with polyvinyl alcohol pores.
[0053] Figure 1 (a), (b), (c), and (d) are electron microscope photos of uncoated polyvinyl alcohol films. Figure 1 (e), (f), (g), and (h) are electron microscope photos of the polyvinyl alcohol film after coating. The scale of (a) and (e) is 100 μm, the scale of (b) and (f) is 10 μm, and the scale of (c), (d), (g), and (h) is 1 μm.
[0054] It can be seen from the figure that the surface smoothness of the PVA film after coating is significantly improved.
[0055] Comparative test example 1
[0056] The polyimide-based membrane is plugged with 184-type silicone rubber, and the silicone rubber coating method is natural immersion. The coated membrane is heat-dried to obtain a polyimide membrane with silicone rubber coating.
[0057] A solvent resistance comparison experiment was conducted on a polyimide film with a silicone rubber coating and a polyimide film with polyvinyl alcohol.
[0058] Petroleum ether was used to carry out an external pressure swelling experiment on the two membranes. The specific experimental steps were as follows: the membrane was installed in a membrane assembly, both ends were sealed with epoxy, petroleum ether was injected on the outside of the membrane, and then the petroleum ether was pressurized to observe whether there was petroleum ether penetrating the inner pores of the hollow membrane.
[0059] The results showed that defects appeared on the surface of the polyimide membrane with silicone rubber coating because the pore-blocking silicone rubber was quickly swollen by petroleum ether. It was soon found that petroleum ether permeated through the hollow fiber membrane and flowed out of the inner tube.
[0060] The polyimide membrane with polyvinyl alcohol was subjected to a continuous experiment at a pressure of 2.0 MPa for 48 hours, and no petroleum ether penetrated the inner tube of the membrane, indicating that the polyimide membrane with polyvinyl alcohol coating blocking the pores has excellent solvent resistance, that is, resistance to heavy hydrocarbon pollution.
[0061] Comparative test example 2
[0062] The polyimide membrane with silicone rubber coating and the polyimide membrane with polyvinyl alcohol were tested for the changes in the permeation separation performance of the polyimide membrane after being contaminated under extreme conditions.
[0063] The polyimide membrane with silicone rubber coating was immersed in petroleum ether with a boiling point of 30.0-60.0℃ for 15 minutes, and then placed in the air naturally for 30 minutes (25.0℃) to allow the free petroleum ether on the surface to evaporate before testing its gas permeation separation performance; the membrane contaminated by petroleum ether was then placed in a vacuum oven at 70.0℃ for 2 hours for drying and then tested its performance to obtain the permeation separation performance of the membrane after decontamination. The specific results are shown in Table 1.
[0064] Table 1 Changes in permeation separation performance after polyimide membrane contamination (25.0℃, 0.50MPa)
[0065]
[0066] From the evolution of the gas permeation separation performance of the membrane in Table 1, it can be seen that after the polyimide membrane was immersed in petroleum ether and contaminated, its separation coefficient for CO2 / CH4 dropped sharply from the initial 35.5 to 16.3, which is only nearly half of the initial value. After vacuum heating to remove petroleum ether, the silicone rubber coating of the membrane was partially damaged by the swelling of petroleum ether, causing pore defects on the surface of the polyimide membrane, resulting in faster gas permeation and reduced separation performance.
[0067] The polyimide film with silicone rubber coating and the polyimide film with polyvinyl alcohol obtained in Example 1 were immersed in petroleum ether.
[0068] Figure 2a The polyimide membrane with silicone rubber coating was immersed in petroleum ether for 20 minutes.
[0069] Figure 2b The following is a photograph of a polyimide film with polyvinyl alcohol immersed in petroleum ether for 30 days.
[0070] It can be seen that the polyimide membrane with silicone rubber coating swelled significantly within 20 minutes and peeled off from the culture dish. At the same time, it showed extremely poor mechanical properties, indicating that the polyimide membrane with silicone rubber coating could not withstand the swelling invasion of petroleum ether. This is the reason why the polyimide membrane cannot tolerate heavy hydrocarbon contamination during the natural gas decarbonization process.
[0071] The polyimide film with polyvinyl alcohol showed extremely excellent stability in petroleum ether. After 30 days of continuous immersion, the polyimide film with polyvinyl alcohol showed no obvious swelling phenomenon and could not be peeled off from the culture dish.
[0072] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A film, characterized in that It includes a base film, a hydrophilic layer, and a hydrophilic functional coating in sequence; The material of the hydrophilic layer is selected from at least one of ethanolamine, diethanolamine, diaminopropanol, diaminobenzoic acid, and 2,4-diaminobenzenesulfonic acid; The material of the hydrophilic functional coating is selected from at least one of cellulose acetate, polyethylene glycol, chitosan, polyvinyl alcohol and polylactic acid.
2. The film according to claim 1, characterized in that The base film is selected from at least one of a polyimide film, a cellulose acetate film, and a polysulfone film.
3. A method for preparing a film according to any one of claims 1 or 2, characterized in that: The following steps are involved: The base film is immersed I in a solvent I solution containing a hydrophilic modifier, dried I, and then immersed II in a solvent II solution containing a hydrophilic functional material and a cross-linking agent, and dried II to obtain the film.
4. The preparation method according to claim 3, characterized in that: The hydrophilic modifier is selected from at least one of ethanolamine, diethanolamine, diaminopropanol, diaminobenzoic acid, and 2,4-diaminobenzenesulfonic acid; The solvent I is selected from at least one of methanol, ethanol and propanol; In the solvent I solution containing the hydrophilic modifier, the concentration of the hydrophilic modifier is 0.01 to 10 wt %.
5. The preparation method according to claim 3, characterized in that: The vacuum degree of the impregnation I is 0-0.1 MPa; The dipping time is 1 to 30 minutes; The drying temperature is 50-120°C; The drying time I is 1 to 120 minutes.
6. The preparation method according to claim 3, characterized in that: The hydrophilic functional material is selected from at least one of cellulose acetate, polyethylene glycol, chitosan, polyvinyl alcohol, and polylactic acid; The cross-linking agent is selected from at least one of glutaraldehyde and boric acid; The solvent II is selected from at least one of acetone, water and ethanol; In the solvent II solution containing the hydrophilic functional material and the cross-linking agent, the concentration of the hydrophilic functional material is 0.01 to 10 wt %; In the solvent II solution containing the hydrophilic functional material and the cross-linking agent, the mass of the cross-linking agent is 5-25 wt % of the mass of the hydrophilic functional material.
7. The preparation method according to claim 3, characterized in that: The vacuum degree of the impregnation II is 0-0.1 MPa; The immersion time of II is 1 to 30 minutes; The temperature of the impregnation II is 0 to 100° C.; The temperature of the drying II is 1 to 100° C.; The drying time II is 1 to 120 minutes.
8. The preparation method according to claim 3, characterized in that: The drying I and the drying II are preceded by washing.
9. The preparation method according to claim 8, characterized in that: The cleaning liquid used for cleaning is selected from at least one of water, ethanol and methanol; The cleaning time is 1 to 30 minutes.
10. Use of the film according to any one of claims 1 or 2, characterized in that: Used for natural gas membrane decarbonization.
Citation Information
Patent Citations
Permanent hydrophilic modification method for surface of porous membrane and porous membrane obtained by same
CN102423642A
Preparation method of hollow fiber membrane for removing carbon dioxide from natural gas
CN111085115A
Carbon dioxide separation membrane and method for producing same
WO2017135230A1